Case report: A rare variant m.4135T>C in the MT-ND1 gene leads to Leber hereditary optic neuropathy and altered respiratory chain supercomplexes - Rákosníková, Tereza; Kelifová, Silvie; Štufková, Hana; Lokvencová, Kateřina; Lišková, Petra; Kousal, Bohdan; Honzík, Tomáš; Hansíková, Hana; Martínek, Václav; Tesařová, Markéta (Frontiers in Genetics, 2023)
Leber hereditary optic neuropathy (LHON) is a primary mitochondrial disease characterized by acute visual loss due to the degeneration of retinal ganglion cells. In this study, we describe a patient carrying a rare missense heteroplasmic variant in the MT-ND1, NC_012920.1:m.4135T>C (p.Tyr277His) manifesting with a typical bilateral painless decrease of visual function, triggered by physical exercise or higher ambient temperature. Functional studies in muscle and fibroblasts show that the amino acid substitution Tyr277 with His leads to only a negligibly decreased level of respiratory chain complex I (CI), but the formation of supercomplexes (SCs) and activity of the enzyme are disturbed noticeably. Our data indicate that although CI is successfully assembled in the patient´s mitochondria, its function is hampered by the m.4135T>C variant, probably by stabilising CI in its inactive form. We conclude that the m.4135T>C variant together with a combination of external factors are necessary to manifest the phenotype.